Language Choice in Intermarriages Indonesian and Japanese: Indonesian Wife's Life Story Study on Language Inheritance in Japan - Ulfah, Elisa; Yoshino, Fumio (Universitas Dian Nuswantoro, 2023)
This study aims to determine the language choice of intermarriage families of Indonesian women and Japanese men in Japan, the factors that determine the language choice, and the implications of language choice. The informants of this study are 8 Indonesian wives who married Japanese men living in Japan. The analysis results show that the primary language used at home is that Japanese wives have a dominant role in determining the language choice in the family. The informants’ mother tongue was deficient and used only in certain situations, namely when angry and joking. This causes children to have difficulty communicating with Indonesian families. Several factors determining the language choice in intermarriage families include residence, wife and husband's language skills, enthusiasm and effort to convey the Indonesian wife's mother tongue to children, Japanese family support, knowledge of language education for children, attitude towards language, psychological situation, and child development. Indonesian wives need knowledge of bilingual education so that children can communicate in Indonesian and Japanese. Therefore, in intermarriages, primary marriages of Indonesian wives and Japanese husbands in Japan, where the environment, facilities, and opportunities to learn Indonesian are limited, it is necessary to plan and discuss with partners how to use the language at home, language education for children, and extra effort if Indonesian wives want the children to have bilingual abilities or to be able to communicate in both the Indonesian and Japanese.